Protease-Activated Receptor (PAR) 1 and PAR4 Differentially Regulate Factor V Expression from Human Platelets - Duvernay, Matthew (The American Society for Pharmacology and Experimental Therapeutics, 2013)
With the recent interest of protease-activated receptors (PAR) 1 and PAR4 as possible targets for the treatment of thrombotic disorders, we compared the efficacy of protease-activated receptor (PAR)1 and PAR4 in the generation of procoagulant phenotypes on platelet membranes. PAR4-activating peptide (AP)–stimulated platelets promoted thrombin generation in plasma up to 5 minutes earlier than PAR1-AP–stimulated platelets. PAR4-AP–mediated factor V (FV) association with the platelet surface was 1.6-fold greater than for PAR1-AP. Moreover, PAR4 stimulation resulted in a 3-fold greater release of microparticles, compared with PAR1 stimulation. More robust FV secretion and microparticle generation with PAR4-AP was attributable to stronger and more sustained phosphorylation of myosin light chain at serine 19 and threonine 18. Inhibition of Rho-kinase reduced PAR4-AP–mediated FV secretion and microparticle generation to PAR1-AP–mediated levels. Thrombin generation assays measuring prothrombinase complex activity demonstrated 1.5-fold higher peak thrombin levels on PAR4-AP–stimulated platelets, compared with PAR1-AP–stimulated platelets. Rho-kinase inhibition reduced PAR4-AP–mediated peak thrombin generation by 25% but had no significant effect on PAR1-AP–mediated thrombin generation. In conclusion, stimulation of PAR4 on platelets leads to faster and more robust thrombin generation, compared with PAR1 stimulation. The greater procoagulant potential is related to more efficient FV release from intracellular stores and microparticle production driven by stronger and more sustained myosin light chain phosphorylation. These data have implications about the role of PAR4 during hemostasis and are clinically relevant in light of recent efforts to develop PAR antagonists to treat thrombotic disorders.